(untitled) (Bioscience Journal, 2018)
Mesenchymal stem cells (MSC) are multipotent cells derived from layer mesoderm and that have potential for self-renewal and cellular differentiation. These cells can be extracted from various tissues, being the main sources the bone marrow (BM) and adipose tissue (AT). Therefore, human Adipose-derived Mesenchymal Stem Cells (AdMSCs) are potentially able to differentiate in several cell types such as neurons, adipocytes and osteoblasts. The objective of this work was to quantify levels of the cytokines TGF-Î²1 and IL-10 in the conditioned medium (CM) of AdMSCs cultivated in 2D and 3D culture after the induction of hypoxia by Cobalt chloride chemistry (CoCl2). When the AdMSCs reached 80% of confluence, the cells were transferred to the 24 plates wells, where they were treated with CoCl2 in 2D and 3D culture. Quantification assay was made using human TGF-Î²1 and IL-10 kits. The analysis was done through the sandwich ELISA assay. The IL-10 and TGF-Î²1 production have increased when the AdMSCs were in three-dimensional culture and under hypoxic conditions, indicating that supplies of oxygen associated to the 3D culture influenced significantly the production of these cytokines. This can be a potent and low-cost strategy to improve Adipose-derived Stem Cells conditioned medium when it comes to the release of IL-10 and TGF-Î² cytokines.